On the structure of groups whose non-abelian subgroups are serial - Dixon, M. R.; Kurdachenko, L. A.; Semko, N. N. (Reports of the National Academy of Sciences of Ukraine, 2016)
We obtain a detailed description of non locally nilpotent locally finite groups, whose non-abelian subgroups are serial, ascendant, or permutable.